Project-Based Learning as an Instructional Approach to Enhance Critical Thinking in Aqidah Akhlaq - Euis Kurniawati; Asrori Asrori; Ika Puspitasari (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
This study examines the implementation of Project-Based Learning (PjBL) in aqidah akhlaq instruction at Azanaya Homeschooling and its contribution to the development of students’ critical thinking skills in Islamic education. The study explores how PjBL is implemented, how Islamic theological concepts—particularly rububiyyatullah and mulkiyyatullah are integrated into project activities, and how facilitators and parents support the development of students’ critical thinking. A descriptive qualitative approach was employed. Data were collected through classroom observations, semi-structured interviews with facilitators and students, and analysis of instructional documents. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, supported by triangulation and member checking. The findings indicate that project-based learning encourages students to engage in authentic inquiry and reflective learning processes that stimulate key components of critical thinking, including problem analysis, interpretation of Islamic theological principles, ethical evaluation, and reflective inference. Through projects related to environmental responsibility and social ethics, students critically connect the concepts of rububiyyatullah and mulkiyyatullah with their roles as khalifah in everyday life. The collaborative partnership between facilitators and parents further strengthens reflective dialogue and supports the development of critical thinking beyond formal learning settings. This study contributes to the literature on Islamic pedagogy by demonstrating that integrating theological concepts within PjBL can function as an effective framework for cultivating critical thinking in aqidah akhlaq education, particularly within alternative learning environments such as homeschooling.